Dynamic Cognitive Learning Theory (DCLT): Paradigma Baru Menuju Pembelajar Adaptif - Sena Kurniawan; Joned Ceilendra Saksana (Lembaga Intelektual Muda (LIM) Maluku, 2026)
The post-truth era and the disruption of artificial intelligence (AI) present major challenges to the digital education ecosystem, where learners are highly vulnerable to algorithmic bias and misinformation. Classical and contemporary learning theories, including connectivism, can be comprehensively expanded to address the internal critical adaptation strategies required by learners in navigating such environments. Therefore, this conceptual study aims to formulate the Dynamic Cognitive Learning Theory (DCLT) to bridge existing theoretical gaps, employing a Systematic Literature Review (SLR) method on 56 reputable scientific publications. The research results formulate DCLT based on three main pillars: Adaptive Cognition for mental flexibility, critical Digital Literacy and Navigation, and Learning Ecosystem Synergy that positions AI as a partner and teachers as cognitive mentors. The learning mechanism operates through four stages: input, evaluation, integration, and reflection. DCLT successfully bridges human internal cognitive capacity with external technological networks. Consequently, DCLT advocates for curriculum restructuring and the adaptation of educators' roles to cultivate epistemically resilient learners in the 21st century. However, this conceptual study is limited as it has not been empirically validated in the field, and its effectiveness is assumed in environments with adequate infrastructure. Therefore, it is recommended that future research empirically test the DCLT operational framework through experimental studies and design more specific instructional models.